Edwards Syndrome and Trisomy 8: a case report of a newborn with multiple congenital anomalies with double aneuploidy - Utari, Agustini; Maharani, Nani; Indriyati, Rita; Sihombing, Nydia Rena Benita; Sarosa, Gatot Irawan; Winarni, Tri Indah (Indonesian Pediatric Society, 2025)
Chromosomal aneuploidy is the most common genetic cause of multiple congenital anomalies (MCA), contributing to high neonatal mortality and morbidity rates in intensive care units. Prevalence of live birth double trisomy is rarely reported, with previous studies reporting the involvement of autosomal aneuploidy combined with sex chromosomal aneuploidy that is a more tolerable or benign phenotype. Mostly, a live-born baby with a double trisomy is associated with mosaicism. This report aims to present a rare case of a viable baby with non-mosaic double autosomal trisomy involving chromosomes 8 and 18. A term baby from advanced maternal and paternal age with low birth weight and height was born from spontaneous vaginal delivery from unremarkable pregnancy. The phenotype was suitable with Edward syndrome with congenital heart anomalies confirmed by cytogenetic analysis with additional extra chromosome 8 (48, XX,+8,+18). The baby was on and off the mechanical ventilator due to respiratory failures, and her health condition gradually deteriorated, leading to her death at the age of 2.5 months due to neonatal pneumonia.